Pangan Fungsional dari Produk Hasil Ternak untuk Meningkatkan Kualitas Kesehatan di Era Pandemi Covid-19 - Lilik Eka Radiati; Dian Laksamana Hati; Dedi Fardiaz (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Radiati LE, Hati DL, Fardiaz D, Sari LRH. 2020. Functional food from animal products to improve health qualityin the era of the covid-19 Pandemic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. 1-11. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Food functional from animal product, provide products important to everyday life, particularly in dietary patterns, to reduce the occurrence of chronic multifactorial diseases. Therefore, the food industry has developed food functional derived from milk and meat fermented products, The products have been the subject of intensive research due to the health benefits. Probiotics as bacterial culture and bioactive peptides as the metabolites in fermentation process. Bioactive peptides usually contain 2 to 20 amino acids residues and as the primary structure of animal proteins, requiring proteolysis for their release from the precursor protein. Release of peptides during fermentation occur in two ways: by the microbial proteolytic system and by endogenous proteolytic enzymes, both of them taking place during the fermentation. Probiotics promote gut health, increase the bio-accessibility of fats and proteins in foods, and bioactive peptides prevent chronic diseases. Bioactive peptides have been shown to antioxidant as radical scavenger and antimicrobial lower the risk of the pathogenic bacteria in the gut. This paper discusses the potential role of bioactive peptide from milk and meat fermented as a functional food acting against pathogenic bacteria in gut and inhibit adipogenesis in obesity. Bioactive peptides exhibit natural resistance to gastrointestinal digestion. Once liberated and absorbed, bioactive peptides may exert a physiological affect on the various systems of the body.